Microcredit and the poor - Kanwar, Swati Batra (Jaipur : Aalekh Publishers, 2012)
With reference to Jodhpur and Nagaur Districts of India.
Includes statistical tables.
Includes bibliographical references and index.
Keywords: Microfinance -- India -- Jodhpur (District); Microfinance -- India -- Nagaur (District); Self-help groups -- India -- Jodhpur (District); Self-help groups -- India -- Nagaur (District); Microfinance -- India -- Jodhpur (District) -- Statistics; Microfinance -- India -- Nagaur (District) -- Statistics; Self-help groups -- India -- Jodhpur (District) -- Statistics; Self-help groups -- India -- Nagaur (District) -- Statistics